Shia Dynamics and Religious Moderation at the Al Hadi Islamic Boarding School in Pekalongan: A Study of Seyyed Hossein Nasr's Perspective - Setiadharmanto, Deddi Fasmadhy; Humaidi, Anis; Syam, Nur (Tebuireng: Journal of Islamic Studies and Society, 2024)
This research aims to analyze the implementation of religious moderation at the Al-Hadi Pekalongan Islamic Boarding School as a response to stigmatization and rejection of Shia beliefs. Using Seyyed Hossein Nasr's theoretical framework which emphasizes balance (tawazun), justice ('adl), and wisdom (hikmah), this research adopts a qualitative method with a case study. This approach involves in-depth interviews, observation, and document analysis. The research results show that the integration of religious moderation teachings in the Islamic boarding school curriculum has succeeded in encouraging tolerant attitudes and constructive 52 Deddy Fasmaddy Setiadharmanto, Anis Humaidi, & Nur Syam political participation, making Al-Hadi Islamic Boarding School a model of religious moderation in Indonesia.